Spontaneous reattachment of Descemet membrane detachment after deep anterior lamellar keratoplasty: A case report. Issue 8 (February 2018) - Lin, Xiaolei; Wu, Yue; Fu, Yana; Dai, Qi
Abstract: Rationale: To report a case of late spontaneous reattachment of Descemet membrane (DM) detachment after deep anterior lamellar keratoplasty (DALK). Patient concerns: A 50-year-old woman with stromal corneal scarring underwent a DALK with the big bubble technique. The DM detachment and double anterior chamber were observed on the first day after operation. Diagnoses: Descemet membrane detachment after deep anterior lamellar keratoplasty [Oculus Dexter (OD), indicates right eye]. Interventions: Sterile air injection was unsuccessful. Conservative observation was performed. Outcomes: During the follow-up, the donor cornea kept transparent and no edema was observed. The DM reattached spontaneously at the fifth months post-DALK. Lessons: The present case suggests that the retained host DM may result in DM detachment after DALK. For the DM detachment without roll rim, the detachment may spontaneously reattach in several months after surgery.